ChemInform Abstract: "(Diphosphine)Nickel"‐Catalyzed Negishi Cross‐Coupling: An Experimental and Theoretical Study. Issue 41 (October 2015) - Nicolas, Emmanuel; Ohleier, Alexia; D'Accriscio, Florian; Pecharman, Anne‐Frederique; Demange, Matthieu; Ribagnac, Philippe; Ballester, Jorge; Gosmini, Corinne; Mezailles, Nicolas
Abstract The nickel‐based catalytic system performs a Negishi‐type cross‐coupling of aryl chlorides with equimolar arylzinc chlorides, demonstrating that strongly electron donating diphosphine ligands are excellent ligands for this process.